Privacy, Property, and Public Sex - Ball, Carlos A. (Columbia Journal of Gender and Law, 2008)
“Making a queer world … require[s] the development of kinds of intimacy that bear no necessary relation to domestic space, to kinship, to the couple form, to property, or to the nation.” The Supreme Court in Lawrence v. Texas relied on a right to sexual liberty to strike down a sodomy statute that criminalized same-sex sexual conduct. In doing so, the Court limited that right in three ways: first, by making it clear that the sex in question has to be consensual; second, that it must be engaged in by adults; and third, that it must take place in the home (or in other similarly private places). In its analysis, the Court found it relevant that the statute reached “the most private human conduct, sexual behavior,.., in the most private of places, the home.” The Court, in effect, equated the home with privacy and privacy with liberty. “Liberty,” the Court noted, “protects the person from unwarranted government intrusions into a dwelling or other private places.” The defendants, the Court added, were free to “choose to enter upon [a sexual] relationship in the confines of their homes and their own private lives and still retain their dignity as free persons.” The Court made clear, however, that if they had instead engaged in “public [sexual] conduct,” then the constitutional right to sexual liberty would have been inapplicable. The geographization of sexual liberty that is evident in Lawrence began forty years earlier in Griswold v. Connecticut, the first case in which the Court applied substantive due process doctrine to sexuality-related issues. The Griswold Court, in analyzing the constitutionality of a law that restricted access to contraceptives, drew a connection between the right of married couples to make decisions affecting their sexual intimacy and the spatial privacy afforded by the marital bedroom. Several years later, in Paris Adult Theater I v. Slaton, the Court rejected the idea that a right to privacy prevented the government from regulating obscene materials shown at a movie theater, noting that “it is unavailing to compare a theater, open to the public for a fee, with the private home…” The Court added that “[t]he idea of a ‘privacy’ right and a place of public accommodation are, in this context, mutually exclusive.”